Optimization of Bacterial Cellulose-Quercetin Biocomposite Synthesis Using The Ex-Situ Method and Its Application as an Antibacterial Agent - Riza Apriani; Gania Ningsih Noer Fajrianti (Helium: Journal of Science and Applied Chemistry, 2025)
Bacterial cellulose is a natural polymer synthesized by bacteria, possessing significant potential for biomedical and pharmaceutical applications. However, it lacks inherent antibacterial properties, necessitating modification with additional materials. Quercetin, a flavonoid compound, is known for its pharmacological activities, including antibacterial effects by disrupting bacterial cell walls. This study aims to identify the antibacterial activity of bacterial cellulose-quercetin biocomposite by optimizing the concentration and modification time, and to characterize their functional groups. Bacterial cellulose was modified using an ex-situ method by immersing it in quercetin solution. Antibacterial testing was performed using the disk diffusion method against Staphylococcus aureus and Escherichia coli. Results indicated that the optimal bacterial cellulose-quercetin biocomposite was achieved at a concentration of 6% with a modification time of 48 hours, showing excellent antibacterial properties with inhibition zones of 18.5 mm for S. aureus and 18 mm for E. coli. FTIR analysis confirmed the main functional groups of cellulose (O-H, C-H, and C-O-C glycosidic bonds) in both bacterial cellulose and the composite, showing no significant changes after immersion in distilled water. This suggests that quercetin binds strongly to the bacterial cellulose matrix, resulting in a stable biocomposite with potential as an effective antibacterial material, such as for wound healing.